Effect of fans and humidifier on temperature and relative humidity in cages - Yusof, T. N. T.; Wayayok, Aimrun; Saufi, M. K. M. (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Acage was developed by attaching fans and humidifier to conduct an experiment on the effect temperature and relative humidity (RH) to simulate a conducive environment on the growth of Green Leaf Hopper (GLH) population. GLH is a pest that spread tungro virus which damages paddy plants and causes a huge loss to paddy farmers. Arduino Uno and DHT22 sensor were placed at inside and outside the cage. The fans and humidifier were set to run at every 15 minutes and the readings were recorded for three days. Comparison of both values of temperature and RH were conducted by t-test to justify the significant level and later to check the influence of the fans and humidifier. Results showed that temperature values significantly dropped to 30.62°C and RH values significantly increased up to 60.60% for the experiment 1. Meanwhile, temperature values significantly dropped to 31.03°C and RH values significantly increased up to 79.05% for the experiment 2 when operating fans and humidifier. This indicated that a controlled system developed based on micro-controller (Arduino Uno) to operate fans and humidifier is successful and can be used to control temperature and RH. This set up can be used for an experiment on the rearing of GLH growth at various levels of temperature and RH.